2015
DOI: 10.1186/s12995-015-0083-4
|View full text |Cite|
|
Sign up to set email alerts
|

Vaccination against hepatitis b virus: are Italian medical students sufficiently protected after the public vaccination programme?

Abstract: BackgroundThe development of a vaccine against hepatitis B virus (HBV) has been a major achievement in terms of prevention of HBV infection. For the present study, we analysed the long-term immunogenicity and effectiveness of HBV vaccination among healthcare students with different working seniorities.MethodsA cross-sectional study of undergraduate and postgraduate students attending the Medical School of the Second University of Naples was conducted between September 2012 and December 2014. HBV serum markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 24 publications
2
26
0
1
Order By: Relevance
“…A recent study among Italian medical students found a similar pattern of vaccination during childhood. A recent study in Greek adolescents aged 11 to 19 has shown a vaccination coverage (HBV) of 96% [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study among Italian medical students found a similar pattern of vaccination during childhood. A recent study in Greek adolescents aged 11 to 19 has shown a vaccination coverage (HBV) of 96% [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies confirm that the acquired immunity persists for at least 10 years after vaccination with level of antibodies > 10 mIU/mL, but probably not longer, if vaccination had been performed at neonatal age [6][7]. In several countries in the world, students of faculties of medicine are examined to establish if the vaccination performed in infancy is still protective several decades after HBV vaccinations, because this is a population occupationallyexposed to a higher risk of acquiring HBV infection [8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Occupational Physicians should consider with particular attention the evaluation of the persistence of anti-HBV specific antibodies in medical students (in most cases vaccinated at birth age) and HCWs specifically at the time of the first employment in order to identify subjects with non-protective anti-HBs titer [32, 33]. Occupational Physicians’ contribution to reduce vaccine delays or refusals and vaccine hesitancy that are also affecting HCWs is crucial [34].…”
Section: Discussionmentioning
confidence: 99%